THE REFLECTIVE SUPERVISION MODEL: AN EFFORT TO INCREASE NURSE JOB SATISFACTION - Santoso Santoso; Rita Kartika Sari; Anggorowati Anggorowati (Belitung Raya Foundation, Indonesia, 2017)
Background: Job satisfaction influences the quality of health services in hospitals. However, low job satisfaction of nurses exists in the literature and influenced by various factors, including supervision. Thus, a reflective supervision model is considered effective in improving nurse job satisfaction. Objective: This study aims to analyze the effect of the reflective supervision model on nurse job satisfaction. Methods: This was a quasi-experimental study with control group design conducted from May to July 2017 at two hospitals at Central Java, Indonesia. There were sixty-eight nurses selected using purposive sampling, with 34 nurses assigned in the experiment and control group. Data were collected using questionnaires and then analyzed by paired t-test. Results: Paired t-test obtained p-value of 0.000, which indicated that the reflective supervision model has a significant influence to nurse work satisfaction. Conclusion: The reflective supervision model has a significant effect in increasing nurse job satisfaction. Therefore, this model could be applied by the head nurses to improve nurse outcome indicator, especially for nurse job satisfaction.